2013
DOI: 10.1097/pai.0b013e31825f4e20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between MDM2 and p53 Alterations in Colorectal Cancer and Their Involvement and Prognostic Value in the Tunisian Population

Abstract: In this work we wanted to highlight the role, which is becoming increasingly important, of MDM2. In fact, we conclude that the effects of MDM2 SNP309 may be considered a valuable prognostic marker to predict poor outcome for Tunisian patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…When the genotype distribution found in the present study was compared to the data for different ethnic origins as demonstrated in Table 3, GG genotype frequency appeared to be similar to Japanese population 21 . GG genotype frequency in this study was higher than that reported in China 23 , Finland 24 , America 24,25 , Italy 20 , Spain 26 , Austria and Poland 27 , Germany 28 , Germany and Romania 29 and lower than in Tunisia 30 and Korea. Moreover, the maximum and minimum GG genotype frequencies recorded in different countries were 30.7% and 7.0%, respectively.…”
Section: Countrycontrasting
confidence: 82%
“…When the genotype distribution found in the present study was compared to the data for different ethnic origins as demonstrated in Table 3, GG genotype frequency appeared to be similar to Japanese population 21 . GG genotype frequency in this study was higher than that reported in China 23 , Finland 24 , America 24,25 , Italy 20 , Spain 26 , Austria and Poland 27 , Germany 28 , Germany and Romania 29 and lower than in Tunisia 30 and Korea. Moreover, the maximum and minimum GG genotype frequencies recorded in different countries were 30.7% and 7.0%, respectively.…”
Section: Countrycontrasting
confidence: 82%
“…24,25 Accumulating evidence indicated that downregulation of MDM2 through various approaches resulted in repressing tumor growth and metastasis, [26][27][28] including CRC. 29,30 MAP4K4 is also involved in activation of c-Jun N-terminal kinase (JNK) pathway. 31 C-Jun, the substrate of JNK, induced expression by phosphorylation of JNK.…”
Section: Introductionmentioning
confidence: 99%
“…According to the exclusion criteria, 5 publications were excluded including 2 publications containing overlapping data [21,22], 1 for not presenting sufficient data for calculating OR and 95% CI [23], and 2 were meta-analysis [11,12]. Manual search of references cited in the eligible studies identified 1 additional article [24].…”
Section: Resultsmentioning
confidence: 99%